ASEAN COUNTRIES SYARIAH BANK INDUSTRY EFFICIENCY LEVEL ANALYSIS USING DATA ENVELOPMENT ANALYSIS (DEA) APPROACH (Indonesia Syariah Bank Industry Readiness Measurement Analysis in Facing AEC) - Pelenkahu, Noldy; Yusuf, Burhanuddin (IJRDO - Journal of Business Management, 2018)
The study aims to analyze syariah bank industry effeciency level of ASEAN countries using Data Envelopment Analysis (DEA) approach and to assess the readiness of Indonesian Islamic banking in facing the ASEAN Economic Community (AEC). The study uses secondary data which was obtained from annual report and financial statement of 2009-2014 period. It used input variables (Deposit, Labor Cost, Fixed Asset) and output variable (Total of Financing and Operational Income). The research result indicates that on average, ASEAN Islamic Bank countries have high category efficiency. It can bee seen in efficiency score of 81.50%. And if it is alanyzed per country, Indonesia has the highest efficiency score of 90.70%; Thailand has 90.04%; Malaysia has 81.99%; Philipines has 58.19%; and Brunei Darussalam has 48.35%. Indonesia Islamic bank actually is able to face free competition in AEC. Meanwhile, it still needs to support with a stronger capital in order to make it more competitively.